Integrated Interactive E-Module for Project-Based Learning to Enhance Independence and Conceptual Understanding of Alternative Energy - Asa Dyah Ayu Nuralita; Bambang Subali; Sunyoto Eko Nugroho; Moh Sidiq (Unnes Science Education Journal, 2025)
This study aims to develop an interactive e-module integrated with the Project-Based Learning (PjBL) model to enhance junior high school students’ independence and understanding of alternative energy concepts. Using the ADDIE-based Research and Development (R&D) method, the process included analysis, design, development, implementation, and evaluation stages. Expert validation, along with readability and practicality tests involving students, was conducted using various instruments, including questionnaires and pretest-posttest evaluations. The e-module achieved high validity, with Aiken's V scores of 0.94 for both media and content. It also gained high readability (84.3%) and practicality (89%) scores. The Wilcoxon test (p < 0.001) and a normalized gain of 0.75 indicated a significant improvement in students’ conceptual understanding. Additionally, the rate of learning independence increased by 85%. The Mann-Whitney test confirmed significant differences between experimental and control groups, proving the module's effectiveness in digital and contextual science learning. Overall, the e-module is effective for project-based science education. The study recommends applying similar approaches in other subjects and integrating advanced technology to support personalized and effective learning in the 21st century.